Fish-Oil–Derived n–3 PUFAs Reduce Inflammatory and Chemotactic Adipokine-Mediated Cross-talk between Co-cultured Murine Splenic CD8+ T Cells and Adipocytes. Issue 4 (4th February 2015) - Monk, Jennifer M; Liddle, Danyelle M; De Boer, Anna A; Brown, Morgan J; Power, Krista A; Ma, David WL; Robinson, Lindsay E
Abstract: Background: Obese adipose tissue (AT) inflammation is characterized by dysregulated adipokine production and immune cell accumulation. Cluster of differentiation (CD) 8 + T cell AT infiltration represents a critical step that precedes macrophage infiltration. n–3 (ω-3) Polyunsaturated fatty acids (PUFAs) exert anti-inflammatory effects in obese AT, thereby disrupting AT inflammatory paracrine signaling. Objective: We assessed the effect of n–3 PUFAs on paracrine interactions between adipocytes and primary CD8 + T cells co-cultured at the cellular ratio observed in obese AT. Methods: C57BL/6 mice were fed either a 3% menhaden fish-oil + 7% safflower oil (FO) diet (wt:wt) or an isocaloric 10% safflower oil (wt:wt) control (CON) for 3 wk, and splenic CD8 + T cells were isolated by positive selection (via magnetic microbeads) and co-cultured with 3T3-L1 adipocytes. Co-cultures were unstimulated (cells alone), T cell receptor stimulated, or lipopolysaccharide (LPS) stimulated for 24 h. Results: In LPS-stimulated co-cultures, FO reduced secreted protein concentrations of interleukin (IL)-6 (−42.6%), tumor necrosis factor α (−67%), macrophage inflammatory protein (MIP) 1α (−52%), MIP-1β (−62%), monocyte chemotactic protein (MCP) 1 (−23%), and MCP-3 (−19%) vs. CON, which coincided with a 74% reduction in macrophage chemotaxis toward secreted chemotaxins in LPS-stimulated FO-enriched co-culture–conditioned media. FO increased mRNA expression of the inflammatory signaling negative regulators monocyte chemoattractant 1–induced protein ( Mc pip ; +9.3-fold) and suppressor of cytokine signaling 3 ( Socs3 ; +1.7-fold), whereas FO reduced activation of inflammatory transcription factors nuclear transcription factor κB (NF-κB) p65 and signal transducer and activator of transcription 3 (STAT3) by 27% and 33%, respectively. Finally, mRNA expression of the inflammasome components Caspase1 (−36.4%), Nod-like receptor family pyrin domain containing 3 ( Nlrp3 ; −99%), and Il1b (−68.8%) were decreased by FO compared with CON ( P ≤ 0.05). Conclusion: FO exerted an anti-inflammatory and antichemotactic effect on the cross-talk between CD8 + T cells and adipocytes and has implications in mitigating macrophage-centered AT-driven components of the obese phenotype.